Aplikasi Diseminasi Penyedia Jasa Private Les Bidang Non Akademik Dissemination Of Non-Academic Private Tutoring Service Providers - Sukry Harly (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
The development of technology is something that cannot be separated from humans at this time, it is based on technology that is increasingly growing. But on the problems faced in the search for facilities and services private tutoring is still an information manual so that it is difficult for the community to find facilities and services for private tutoring especially in non-academic fields. Then it needs to be specifically designed as a search system for facilities and private tutoring services through web-based media. Thus the community is not difficult to find a place or non-academic field private tutoring services because in this system there is a latitude of maps that will show the location and there are display fees and online payments via a bank account. In designing the system the author observes the company and the community as well as a bibliography that aims to be a benchmark. The author uses the Business Model Canvas (BMC) method with the support of system requirements elicitation, as well as modeling the Unified Modeling Language (UML) system to visually implement the Hypertext Preprocessor (PHP) program language with the MySQL database as a database server. With the design of a search system for facilities and private tutoring services, it can make it easier for people to find effective and efficient facilities or services in non-academic fields.